Rasionalitas Masyarakat Desa Sidorejo Terhadap Aktivitas Remaja Karang Taruna dalam Pembentukan Akhlak di Masa Pandemi - Sustianing Solicha; Agus Machfud Fauzi (TARLIM : JURNAL PENDIDIKAN AGAMA ISLAM, 2021)
During this pandemic, the morality of teenagers in Sidorejo Village is concerning. That is, their morality is getting worse. At the same time, many organizations in Sidorejo Village are not developing well. Adolescence is a period where individuals seek a way of life, accept moral (ethical) norms as well as religious and aesthetic norms. Many have limitations, however, thereby making their external activities depend on others. This contradictory situation goes hand in hand, and constitute the background of this study. The present study aims to figure out how people living in Sidorejo Village react to the behavior of the youth group in forming their morality during the pandemic. This study is informed by the theory of social action proposed by Max Weber. The study is a case study using a qualitative approach with data collection techniques involving interviews. The results showed that only some of the youth who were participants in the youth organization were willing to take part in these activities due to being member activities held in schools or others. The role of the community is to guide the holding of religious activities such as reading the Qur'an and memorizing via virtual means. The results showed that the formation of adolescent morals have both good and not so good characters, which means that many teenagers participate in those activities but also spend their times doing things that are not useful.